BADANIA ROMANISTÓW POLSKICH W LATACH 2011-2013 - Maria Zabłocka (Zeszyty Prawnicze)
Polish Romanists' Research Work, 2011-2013 Summary A look at the research done by Polish Romanists in the 21st century and its effects in the form of publications and progress on the academic ladder confirms the claim that Poland continues to be one of the leading countries for scholarship in Roman law. In the first decade of the century four Polish scholars of Roman law were appointed to full professorships, seven gained their post-doctoral habilitation degrees, and forty-five were awarded the doctor’s degree. The figures for the past three and a half years are respectively four professorships (with a further two waiting for the formality of the President’s signature on the appointment), eight habilitations, and twelve doctorates. A characteristic feature marking recent years has been an unprecedented number of translations (into Polish) of source texts, usually accompanied by an extensive commentary. The main achievement in this area has been the translation of the Digests by a team of lawyers and linguists. Alongside the publication of source texts and collective volumes, the past years have also seen the issue of thirty-three monographs and hundreds of articles on a variety of subjects, but one of the characteristic features has been an unprecedented interest in public law, especially criminal law, which has given rise to eight monographs in three years. Unfortunately, certain tendencies have given cause for concern, as quantity is not always tantamount to quality. A lot of articles do not come up to the required standard and call for improvement as regards references and recent literature (especially Polish publications) cited, writing style, and a more critical approach to their subject. Many articles offer an oversimplified comparison of a contemporary legal institution with aspects of Roman law. Occasionally suggestions are made that only subjects which are directly related to today’s issues should be addressed. Time will tell whether this is the right attitude to take.